Customer loyalty: an exploration of the relationship between service quality and customer intent to return / Ainiwati Bakeri - Bakeri, Ainiwati (Faculty of Business and Management, 2009)
In today's competitive marketplace, one of the biggest concerns of service restaurant operators is winning customer loyalty. This study examined the relationship between service quality and customer intent to return in the full-service sector of the restaurant industry in Sri Petaling, Kuala Lumpur. The constructs of service quality and customer intent to return were measured using DINESERV survey instrument. Evidence exists that service quality delivery through five service quality dimension is an essential strategy to success, possibly more important than low price. To deliver superior service quality, managers of restaurant must first understand how customers perceive and evaluate customer service. The goals of this article are to review and synthesize the literature about service quality delivery through service quality dimension, and creating customer loyalty in service restaurant industry.